GAMBARAN SELF-ESTEEM PESERTA DIDIK KELAS VIII DI SMPN 5 CIMAHI - Anisa Oktavia; Sobari, Teti; Pahlevi, Reza (IKIP Siliwangi, 2024)
The problem that often occurs in students is that they are unable to understand the extent to which they consider themselves worthy, valuable and believe in their abilities or competencies that lead to self-esteem. This study aims to represent the profile of the level of self-esteem in class VIII students at SMPN 5 Cimahi. This study used a descriptive quantitative approach. The sample used was 135 class VIII, sampling using simple random sampling. The data collection method uses a self-esteem questionnaire that refers to the theory of Christopher J. Mruk. Data were analyzed based on overall profile, self-esteem aspects, and gender. The results showed that the self-esteem profile of VIII grade students at SMPN 5 Cimahi was in the moderate category with a total of 89 students, in the high category of 21 students, and in the low category of 25 students. The conclusion of the study found that the competence aspect of students in the high category is more than the worthiness aspect. Meanwhile, based on gender, it shows that low self-esteem is experienced more by female students.